2014
DOI: 10.1021/jz500798m
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Self-Propelling of Small-Scale Condensed Microdrops by Closely Packed ZnO Nanoneedles

Abstract: Realizing the efficient self-propelling of small-scale condensed microdrops is very challenging but extremely important to design and develop advanced condensation heat transfer nanomaterials and devices, for example, for power generation and thermal management. Here, we present the efficient self-propelling of small-scale condensed microdrops on the surface of closely packed ZnO nanoneedles, as-synthesized by facile, rapid, and inexpensive wet chemical crystal growth followed by hydrophobic modification. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 32 publications
0
134
0
Order By: Relevance
“…However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values. Later, researchers noted that the energy dissipation caused by viscous flow (E vis ) and interface adhesion (E int ) must be considered, [31,[56][57][58][59][60] while gravi tational potential energy may be neglected due to microdrop sizes that are far smaller than the capillary length. Very recently, our group further found that, besides the solid-liquid van der Waals attraction, nanoscale line tension at three-phase contact lines cannot be neglected in calculating adhesioninduced dissipation.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the experimental velocities of the self-jumped microdrops are apparently smaller than their theoretical values. Later, researchers noted that the energy dissipation caused by viscous flow (E vis ) and interface adhesion (E int ) must be considered, [31,[56][57][58][59][60] while gravi tational potential energy may be neglected due to microdrop sizes that are far smaller than the capillary length. Very recently, our group further found that, besides the solid-liquid van der Waals attraction, nanoscale line tension at three-phase contact lines cannot be neglected in calculating adhesioninduced dissipation.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
“…Very recently, our group further found that, besides the solid-liquid van der Waals attraction, nanoscale line tension at three-phase contact lines cannot be neglected in calculating adhesioninduced dissipation. [31] As shown in a simplified model that only considers the merging of two microdrops with identical diameters (Figure 2a-d), excess energy can be generated as the released surface energy deducts the viscous-flow-induced energy dissipation. In principle, the merged microdrop can selfremove as long as the excess surface energy is greater than the energy dissipation caused by interface adhesion.…”
Section: Cmdsp Mechanismmentioning
confidence: 99%
See 3 more Smart Citations